THE COMBINED EFFECT OF SUCKLING SYSTEM AND WEANING WEIGHT ON MILK TRAITS OF NATIVE SHEEP - & Alkass, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Data of the current stud, were collected on 32 Iraqi native sheep aged 2-5 years maintained on commercial flock. At lambing, the 32 ewes were divided into two equal groups, lambs in the 1st group were left with their dams till weaning and then were milked twice daily till they dry off (Continuous), whereas the 2nd group, lambs were separated at night for 12 hr. and the ewes were milked once daily at morning (Restricted). Then each main group was subdivided into two group to be weaned their lambs when they reached 3 or 4 times of their birth weight (WB1 and WB2). Results revealed that ewes of restricted suckling produced significantly (P < 0.05) more post weaning (80.80 vs.49.44 L), total milk yield (135.01 vs. 109.94 L) and sealable milk (99.86 vs. 49.44 L) and had significantly longer lactation period (169.3 vs. 140.2 days) compared ewes in continuous suckling. Also, results obtained indicate that daily gain in weight averaged 0.23 kg from birth to weaning and from birth to marketing and 0.24 kg from weaning to marketing and neither suckling system nor weaning weight affected these trait significantly. It can be concluded that restricted suckling resulted in an increase in sealable milk without any adverse effect on growth of lambs.